Gluten-free Diet and Behavioral Well-being in People with Autism Spectrum Disorder: A Systematic Review (Papeles, 2026)
Introduction: Autism spectrum disorder (ASD) is a neurodevelopmental condition characterized by difficulties in social interaction, communication, and repetitive behavioral patterns that directly impact the socio-emotional well-being of students. The gut-brain axis has been proposed as a mechanism through which a gluten-free diet (GFD) may influence behavior in individuals with ASD. Methodology: A systematic review was conducted following the PRISMA protocol, searching five databases (EBSCO, Dialnet, WOS, Scielo, Scopus) with Boolean combinations of “diet”, “gluten” and “autism”. After applying inclusion/exclusion criteria, 13 studies published between 2006 and 2023 were selected. Results and discussion: The findings are heterogeneous. Most quantitative studies did not report statistically significant improvements; however, parents, teachers, and caregivers consistently noted positive changes in language, hyperactivity, social interaction, and stereotyped behaviors. Studies with longer follow-up and gastrointestinal symptom profiles showed greater benefits. Conclusions: The GFD may be a complementary therapeutic strategy for certain individuals with ASD, particularly those with gastrointestinal comorbidities. Closer collaboration among educators, families, and health professionals is essential for its successful implementation.
Keywords: Autism spectrum disorder; gluten-free diet; behavior; systematic review; well-being